Pengaruh Pembenaran Medis tentang Kapan Kehidupan Dimulai Terhadap Pengaturan Hukum tentang Anak dalam Kandungan - Paulinus Soge (Fakultas Hukum Universitas Islam Indonesia, 2012)
The existence of abortion is more frequent in cities than in villages, and most of abortions are done deliberatively, especially in the cities. The problems which will be studied are: First, when does life begin based on the medical study? Second, how should the prevailing laws (ius constiuendum) be to protect the unborn child? Related to the protection for unborn child, the research using normative method has already been conducted. The research result shows that: first, life begins since the conception based on the medical finding. Second, as the result, Article 75 verse (2) b of Law of Health both horizontally and vertically is not synchronous with the prevailing regulations of law. For the legal assurance, Article 75 verse (2) b of Law of Health needs to be reviewed.